EOLA1 Inhibits Lipopolysaccharide-Induced Vascular Cell Adhesion Molecule-1 Expression by Association with MT2A in ECV304 Cells - Weiling Leng; Xiaotian Lei; Hao Meng; Xinshou Ouyang; Ziwen Liang (International Journal of Inflammation)
Our research group firstly discovered endothelial-overexpressed lipopolysaccharide-associated factor 1 (EOLA1, GenBank number AY074889) as a lipopolysaccharide (LPS) responsive gene in ECV304 cells. The previous studies have further demonstrated the association of EOLA1 with metallothionein 2A (MT2A), while the role of EOLA1 during LPS-induced inflammatory response in ECV304 cells is unknown. In this report, we determined the subcellular localization of EOLA1 and the regulatory capacity of EOLA1 on vascular cell adhesion molecule-1 (VCAM-1) in response to LPS in ECV304 cells. Our results show that EOLA1 is broadly diffuse in the cells, and EOLA1 expression is dramatically induced by LPS. EOLA1 knockdown results in significant enhancement of LPS-induced VCAM-1 production. Consistent with this, overexpression of EOLA1 leads to the reduction of LPS-induced VCAM-1 production. Furthermore, MT2A knockdown reduces LPS-induced VCAM-1 production. Collectively, our results demonstrate a negative regulatory role of EOLA1 on LPS-induced VCAM-1 expression involving its association with MT2A in ECV304 cells.